0
$\begingroup$

$$\frac{\sin^2 (2\alpha)}{\sin^2 (\alpha)}=4-4\sin^2 (\alpha)$$

I have to solve the left hand side to equal the right hand side.

$\endgroup$
  • $\begingroup$ What identities are you familiar with? $\endgroup$ – Git Gud Mar 13 '14 at 14:18
  • $\begingroup$ I know all of them I just used the wrong one so I got a wrong answer $\endgroup$ – Aly Mar 13 '14 at 14:24
  • $\begingroup$ definitely was overthinking this one because it makes so much sense now $\endgroup$ – Aly Mar 13 '14 at 14:36
2
$\begingroup$

We have $\sin(2\alpha) = 2 \sin \alpha \cos \alpha$, hence $$ \frac{\sin^2(2\alpha)}{\sin^2(\alpha)} = \frac{4 \sin^2 (\alpha) \cos ^2 (\alpha)}{\sin^2(\alpha)} = 4 \cos^2 \alpha = 4 - 4\sin^2 \alpha $$ as $\cos^2 \alpha + \sin^2 \alpha = 1$.

$\endgroup$
  • $\begingroup$ (+1) someone is rage downvoting? $\endgroup$ – Guy Mar 13 '14 at 14:34
2
$\begingroup$

Left-hand side: $\sin (2t) = 2\sin(t)\cos(t)$, so $$\sin^2(2t) = (\sin (2t))^2 = (2\sin t\cos t)^2 = 4\sin^2 t \cos^2 t$$

That gives us $$\dfrac{\sin^2(2t)}{\sin^2 t} = \require{cancel}\dfrac{4\cancel{\sin^2 t} \cos^2 t}{\cancel{\sin^2 t}} = 4\cos^2 t$$

On the right-hand side, note that $$4-4\sin^2 t = 4(1-\sin^2 t) = 4\cos^2 t$$

$\endgroup$
  • $\begingroup$ Could someone please explain the down-vote? $\endgroup$ – amWhy Mar 13 '14 at 14:26
  • $\begingroup$ I have no idea. I will upvote you for two reasons, 1) to cancel that uncalled for downvote. 2)supercool cancellation. $\endgroup$ – Guy Mar 13 '14 at 14:31
  • $\begingroup$ I do the same ! $\endgroup$ – Claude Leibovici Mar 13 '14 at 15:45
0
$\begingroup$

HINT:

Use Double angle formula $$\sin2x=2\sin x\cos x$$

Then, Fundamental Theorem of Trigonometry

$\endgroup$
0
$\begingroup$

$$\frac{\sin^2(2\alpha)}{\sin^2(\alpha)} = \left(\frac{\sin(2\alpha)}{\sin(\alpha)}\right)^2 = \left(\require{cancel}\frac{2\cancel{\sin(\alpha)}\cos(\alpha)}{\cancel{\sin(\alpha)}}\right)^2= 4\cos^2(\alpha) = 4 - 4\sin^2(\alpha)$$

List of idenitities used:

  • $\sin(2\alpha)=2\sin(\alpha)\cos(\alpha)$
  • $\sin^2(\alpha)+\cos^2(\alpha) = 1$
$\endgroup$
0
$\begingroup$

Using $\sin x =\frac{e^{ix}-e^{-ix}}{2i}$ and $\cos x =\frac{e^{ix}+e^{-ix}}{2}$, and $\sin^2 x + \cos^2 x = 1$, write

$$\boxed{\dfrac{\sin^2 2\alpha}{\sin^2 \alpha}} = \left(\frac{\sin 2\alpha}{\sin \alpha}\right)^2 = \left(\frac{(e^{2i\alpha}-e^{-2i\alpha})/2i}{(e^{i\alpha}-e^{-i\alpha})/2i}\right)^2$$

$$ = \left(\frac{(e^{i\alpha}+e^{-i\alpha})(e^{i\alpha}-e^{-i\alpha})}{(e^{i\alpha}-e^{-i\alpha})}\right)^2 = \left(e^{i\alpha}+e^{-i\alpha}\right)^2=\left(2\cdot\left(\frac{e^{i\alpha}+e^{-i\alpha}}{2}\right)\right)^2$$

$$ = 4\cos^2 \alpha = 4(1-\sin^2\alpha) = \boxed{4 - 4\sin^2 \alpha}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.